Forgotten effects model and exchange risk exposure at manufacturing smes (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2016)
In a globalized environment, uncertainty permeates the performance of modern economies, this condition affects all organizations, regardless of the activity, size or location, therefore the propensity to suffer the consequences of volatility phenomena, including the exchange rate, it is a reality, the operation of small and medium enterprises are no exception, its existence is affected by unexpected changes in the exchange rate. In this paper, are identified the factors that motivate exposure of manufacturing SMEs using a model based on the principles of the theory of fuzzy subsets, called Forgotten Effects. The use of this methodology has allowed obtain qualitative information derived from the appreciation of a group of expert, whose knowledge comes from everyday experience, characteristic awarded the empiricism necessary for scientific contextualization. It has been found that factors such as: a) lack of information, b) poor financial planning, c) proprietor behavior, through other factors such as: inflation, lack of culture of protection, unemployment and oil prices, influence for SMEs are exposed to unexpected variations in the exchange rate.
Keywords: exposure; currency risk; forgotten effects; fuzzy logic